(untitled) (Al-Academy, 2025)
Cinema has become a fertile ground for dealing with various humanitarian topics, no matter how complex and thorny they are, from psychological to social and political topics. It is no secret to anyone that cinema has been used to pass on many political ideologies, especially in the period after World War II and the Cold War period until the present day, and anarchism was one of those ideologies that Films have dealt with it, whether negatively or positively, and it is a basic theme in films that come from the places of its establishment and application as an alternative political system to the conventional ruling regimes, such as Japan, the United States of America, Spain, and France. These films are popular on both the elite and popular levels, especially the latter, which complements them with their innovative artistic forms. And the unusual ways of narrating it and the constant innovation of new formulations at the level of photography, camera movements, montage, and visual and audio effects that play the main role in this type of film. Hence, the researcher determined the title of her research entitled (The significance of anarchist representations in the structure of the contemporary feature film). The research was according to the methods The scientific research consists of five chapters, which the researcher classified according to the following structure:The first chapter was entitled (The methodological framework) for the research, which included the research problem and the need for it. The researcher formulated the research problem according to the following question: What are the implications of anarchist representations in the structure of contemporary feature films?The chapter also included the importance of the research and the goals it seeks to achieve, as well as the limits of the research that the researcher relied on in choosing the purposive sample among the reasons stated in the body of the research, which are the time limits that she specified in the first decade of the new millennium and the location limits that the researcher specified in the countries that produce the most prolific films. Which takes anarchism as its basic theme, which is the United States of America, as well as the objective limit of studying anarchist representations and their implications in the structure of contemporary narrative films.As for the second chapter (the theoretical framework and previous studies), the researcher divided it into two sections, the first under the name (anarchism in film discourse), in which the origins of anarchism were discussed, the term and concept were clarified, the most important theorists of the anarchist movement were dealt with, the historical extrapolation of the revolutionary anarchist movement, and the most important schools of anarchist thought (political anarchism) were clarified. (religious and theoretical) and to show the most important centers of its practical applications in the world throughout modern times and in ancient civilizations such as China, Greece and Islamic anarchism. Then the researcher turned to historical extrapolation of the representations of anarchism in cinematic films from the era of silent cinema until the era of digital. The second was titled (The Structure of the Contemporary Narrative Film). In it, the researcher discussed the concept of the contemporary film and its most important features and characteristics, and mentioned the most important contemporary narrative films that made a shift in its approach to narrative and film form. The researcher presented a group of film examples such as the film Fight Club, the film The Dark Knight, the film Joker, the film The Purge in its three parts, and others. From the films, the researcher extracted through the two studies a set of indicators that were mentioned at the end of the chapter, including1. The idea of anarchism grows in the film and is represented by the use of double codes as techniques whose connotations are intertwined in the structure of the femme narration.2. Manipulating the narrative structure of the film through a context full of disintegration and distraction to highlight and confirm the anarchist connotations.The third chapter (research procedures) dealt with the research methodology, the research community, the research tool, the unit of analysis, the validity of the tool, and the analysis steps. Then came the fourth chapter, which specializes in analyzing and discussing the research sample. In this chapter, the researcher applied the research tool to the intentional research sample, which the researcher chose from the research community, and it was the movie V for Vendetta, produced in 2006. It was analyzed to come up with results and conclusions.As for the fifth chapter, which was entitled (Results and Conclusions), the researcher discussed the results and conclusions she reached after applying the research tool. As for the results she reached:1. The ideas of anarchism in the film in the research sample challenge traditional concepts of violence in cinema2. The representations of narcissism in contemporary film depend on the deconstruction of the series of events that are interconnected in traditional structures.